2008
DOI: 10.1097/01.ccm.0000297956.27474.9d
|View full text |Cite
|
Sign up to set email alerts
|

Empiric antibiotic therapy for suspected ventilator-associated pneumonia: A systematic review and meta-analysis of randomized trials

Abstract: Monotherapy is not inferior to combination therapy in the empirical treatment of VAP. Available data neither identify a superior empirical regimen nor conclusively conclude that available regimens result in equivalent outcomes. Larger and more rigorous trials evaluating the choice of, and even need for, empirical therapy for VAP are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 84 publications
1
56
1
6
Order By: Relevance
“…Indeed, even though most cases in the moderate group were given monotherapy (85.7%), 30-day survival rates (95.2%) were generally good compared with those of CAP patients [12]. Furthermore, the many studies of pneumonia [20,21] have shown no significant differences in outcomes between monotherapy and combination therapy. These results suggest that we need the new strategy based on prognostication.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, even though most cases in the moderate group were given monotherapy (85.7%), 30-day survival rates (95.2%) were generally good compared with those of CAP patients [12]. Furthermore, the many studies of pneumonia [20,21] have shown no significant differences in outcomes between monotherapy and combination therapy. These results suggest that we need the new strategy based on prognostication.…”
Section: Discussionmentioning
confidence: 89%
“…Systematic review and other overviews have tried to compile existing clinical evidence on the effects of combination therapy [4][5][6][7][8][9][10][11][12]. In general, meta-analyses of observational studies have shown a benefit for combination therapy [8,11], whilst those including randomised controlled trials (RCTs) have not [4][5][6][7]9,10,12]. These reviews approached the question from different perspectives, each addressing a specific clinical scenario [Gram-negative bacteraemia, febrile neutropenia, empirical treatment of sepsis, endocarditis, ventilator-associated pneumonia, cystic fibrosis (CF)], with different study designs, different definitions of combination therapy and different outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines discussed invasive quantitative cultures as having some advantage over endotracheal aspirates for the diagnosis of VAP, but subsequent studies did not show any difference in mortality for either approach [5]. Recently, investigators have raised concerns about adherence to the guideline recommendation of using routine combination therapy for VAP [6,7]. Prevention strategies based a group of interventions lumped into a 'daily bundle' have been shown to decrease the rate of VAP [8].…”
Section: Introductionmentioning
confidence: 99%